Kempf Varieties - Lakshmi Bai, V. (The Journal of the Indian Mathematical Society, 1976)
This paper is a sequel to [7]. Let G be a connected, semisimple linear algebraic group defined over an algebraically closed field k, of arbitrary characteristic.